Efficacy of silver diamine fluoride on immediate and delayed adhesive strength of resin composite to sound dentin of permanent teeth: an in vitro study (Mustansiria Dental Journal, 2024)
Objectives: How silver diamine fluoride affected the immediate and prolonged adhesive resin composite's resistance to sound dentin of permanent premolars. Procedures: Three groups were identified (total number=30). The manufacturer's recommendations were followed while applying adhesive resin to the dentin surfaces in Group A after they had been etched. In Group B and C, dentin surfaces were treated with silver diamine fluoride and 0.05% NaF respectively. Then etched and bonded as for the control group. Then resin composite build-ups were created. Following this, each group was divided into two subgroups (for each group n=5), subgroup 1 underwent a shear bond strength test by universal test machine after 24 hrs, subgroups 2 the test was done after thermocycling process (300 cycles). The mode of failure was also examined. Results: The type of dentin surface treated with SDF solution was significantly affect shear bond strength (p=0.000) for both periods (immediate and prolonged). However, there were no significant difference between NaF group and control group on shear bond strength (p